Quest for Political Stability: Party Leadership Role in CA - Marattha, Purushotam (Tribhuvan University Journal, 2016)
The political parties of Nepal have never been able to move as an engine of social transformation process, much like their inability to give a stable government. After replacing the Party-less regimes, with them multiparty system the country has mainly witnessed drawbacks of parliamentary system. The political parties have failed to promote democracy and they have hammered on the root of constitution. However, a new constitution was demanded through a Constituent Assembly (CA) and after nearly a decade long exercise, the constitution of Nepal, 2015, was promulgated on September20, 2015. Since that period Nepal has formally entered into a Federal Republican Nation. The new constitution has covered all the achievements of Second People's Movement (SPM).Since then the federal republican constitution has been completely setup in Nepal. This constitution has institutionalized the federal democratic republican setup and it has opened the rooms for amendment, where as the constitution of the Kingdom of Nepal, 1990 was not amended even a single article for the last many years. Writing the constitution through the CA was a great achievement of Nepal. During the constitution declaration period major political forces like Big-3 NC, CPNUML and UCPNM showed their highest degree of Unity. The new constitution was passed by more than two thirds majority in the CA. But the Conflict about the number of States (Pradesh) is hampering the stability of the present new constitution. The dissolved CA-2 has not been able to settle all the political conflicts. The on going Madhes agitation deepen into the another constitutional crisis. Tarai based parties like Samyukta LoktantrikMadhesi Morcha (SLMM), an alliance of four parties has joined the parliamentary process. Earlier SLMM has obstructed and paralyzed border area with an unseen support of southern neighbor. Daily general strike of SLMM and closure of industries at border points has led to soft state syndrome in Nepal.